Stefan Zweig : A Bibliography - Klawiter, Randolph J. (Chapel Hill The University of North Carolina Press, 1965)
Originally published in 1965, this volume presented the only comprehensive bibliography of the writings of the Austrian novelist, journalist, and playwright Stefan Zweig and of the books and articles about his work.
Andrew W. Mellon Foundation
National Endowment for the Humanities
English
Keywords: Anthologies (non-poetry); German Studies; Literature